ANALISIS KINERJA OPERASIONAL DEWAN PENGAWAS SYARIAH (DPS) PADA KSPPS BMT SRI SEJAHTERA JAWA TIMUR - Putri Pratama, Agustina Sintya (Jurnal Ekonomika dan Bisnis Islam, 2020)
Shariah Supervisory Board (DPS) is the most important part in Islamic financialinstitutions and is the guarator of the implementation of shariah principles in accordancewith Minister of Cooperatives and Small Medium Entreprises RegulationNo.11/PER/M.KUKM/XII/2017 concerning the Implementation of Sharia Loan Savingsand Loan Business Activities which requires the Sharia Supervisory Board (DPS). Inaddition there are requirements specified in Minister of Cooperatives RegulationNo.16/PER/M.KUKM/IX/2015 concerning the Implementatuon of Savings and LoanBusiness Activities Financing bu Cooperatives that must be met so that there are noirregularities in any sharia cooperatives activities. This study uses descriptive qualitativemethods that aim to determine the performance of the Sharia Supervisory Board (DPS) inoperational activities at KSPPS BMT Sri Sejahtera Jawa Timur. From the results if theresearch conducted that supervision activities carried out by the Sharia SupervisoryBoard (DPS) with direct supervision through reports from managers can be said to beless that optimal because supervision activities carried out are flexible and not onlycarried out on one Islamic financial institutions. In addition, public insight about theimportance of the Sharia Supervisory Board (DPS) is less than optimal.